2012
DOI: 10.1590/s0100-204x2012000300005
|View full text |Cite
|
Sign up to set email alerts
|

Short-term storage in vitro and large-scale propagation of grapevine genotypes

Abstract: -The objective of this work was to evaluate the large-scale propagation of grapevine genotypes after short-term storage in vitro. Microshoots from ten grapevine genotypes were used. The following storage temperatures were evaluated: 10, 20, and 25°C. After short-term storage, the shoots were propagated in up to five successive subcultures, to assess the large-scale propagation of the germplasm maintained under conditions of minimal growth. The propagated shoots were rooted in different concentrations of indolb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Similar results have been reported by Silva, Luis and Scherwinski-Pereira (2012), who showed that grapevine genotypes can be stored in vitro for six months in WPM medium at 20°C light intensity of 38 μmol m Studies on in vitro conservation have shown promising results that suggest longer intervals between subcultures is possible. In sugarcane, Lemos et al (2002) reported that it is possible to conserve microplants under slow-growth conditions for 12 months when they are maintained at a temperature of 15°C light intensity of 50 μmol m -2 s -1 and a 16 hours photoperiod.…”
Section: Resultssupporting
confidence: 87%
“…Similar results have been reported by Silva, Luis and Scherwinski-Pereira (2012), who showed that grapevine genotypes can be stored in vitro for six months in WPM medium at 20°C light intensity of 38 μmol m Studies on in vitro conservation have shown promising results that suggest longer intervals between subcultures is possible. In sugarcane, Lemos et al (2002) reported that it is possible to conserve microplants under slow-growth conditions for 12 months when they are maintained at a temperature of 15°C light intensity of 50 μmol m -2 s -1 and a 16 hours photoperiod.…”
Section: Resultssupporting
confidence: 87%
“…There are several reports in the literature highlighting the impact of low temperatures on the in vitro conservation of different plants: Piper aduncum and Piper hispidinervum [5], vetiver [6], sugarcane [4], grapevine [7], and Drosophyllum lusitanicum [8]. …”
Section: Resultsmentioning
confidence: 99%
“…These authors point out, as a general rule, that the minimum storage temperature of a plant depends on the geographical conditions under which the species grows. Furthermore, Silva, Gomes & Scherwinski (2012), suggest that the storage temperature should be between 4 and 10°C for those cultures that normally grow at 20-25 ° C and between 15 and 20°C for those growing at 30°C. In the conservation of papaya (Carica papaya L.) apices, which grows in natural conditions at temperatures of approximately 30°C, Suksa, Kataoka, Fujime & Subhadrabandhu (1997), achieved high survival rates after 12 months of culture at 16°C.…”
Section: Discussionmentioning
confidence: 99%